Macroprudential Stress Tests and Policies : Searching for Robust and Implementable Frameworks - Anderson, Ron (IMF Working Papers; Working Paper ;, 2018)
Macroprudential stress testing (MaPST) is becoming firmly embedded in the post-crisis policy-frameworks of financial-sectors around the world. MaPSTs can offer quantitative, forward-looking assessments of the resilience of financial systems as a whole, to particularly adverse shocks. Therefore, they are well suited to support the surveillance of macrofinancial vulnerabilities and to inform the use of macroprudential policy-instruments. This report summarizes the findings of a joint-research effort by MCM and the Systemic-Risk-Centre, which aimed at (i) presenting state-of-the-art approaches on MaPST, including modeling and implementation-challenges; (ii) providing a roadmap for future-research, and; (iii) discussing the potential uses of MaPST to support policy.